Health-related quality of life and associated factors among patients with beta thalassemia attending three government hospitals in Selangor, Malaysia - Md Yusof, Asauji Yusnuryati (2011)
Beta thalassemia is the most prevalent of all human genetic disease. In Malaysia, 600,000 carriers of beta thalassemia were reported. Each year, between 150 and 350 babies were born with beta thalassemia which mainly was Malay and Chinese. There were also about 5,600 blood transfusion dependent patients in Malaysia. The aim of the present study was to determine the health related quality of life among patients with beta thalassemia and its associated factors. A cross-sectional study was conducted among patients with beta thalassemia who attended the Paediatric Clinics, Hospital Tengku Ampuan Rahimah, Hospital Serdang and Hospital Kajang in Selangor, Malaysia. Patients between the age of eight and 18 years old were invited to participate in the study. Data was collected using a pretested structured questionnaire which included the socio-demographic profile of the participants, medical information and a validated Paediatric Quality of Life Inventory 4.0 (PedsQL version 4.0) which verbal and written consents were obtained from the patients and their parents. Data were analysed using Statistical Package Science System version 16.0 (SPSS version 16.0). A significant level was determined at p value less than 0.05. The respondents were 70 beta thalassemia patients who fulfilled the inclusion criteria with a response rate of 97.2%. Majority 51 (72.9%) of the respondents were between eight to 12 years old, 52.9% were male and majority 87.1% were Malay. Most of the respondents had three or more siblings (65.7%) and did not have other siblings with beta thalassemia (65.7%). Mostly they were beta thalassemia major (58.6%) with less than 11 years duration of illness (58.6%) and received blood transfusion also desferrioxamine treatment (71.4%). The lowest scores from all six domains of health related quality of life was school functioning (58.93 ± 17.93). This present study indicated that physical functioning was associated with types of beta thalassemia (p = 0.005), types of treatment (p = 0.001) and side effects of desferrioxamine treatment (p = 0.001). The emotional functioning of this study was significantly associated with age, education level and duration of illness with p = 0.003 respectively also the types of treatment (p = 0.002). The social functioning significantly associated with age (p = 0.014), race (p = 0.011), especially Indian which compared with Malay the p = 0.004 and compared the Indian with Chinese the p = 0.024, other than that were education level (p = 0.014), types of beta thalassemia (p = 0.007), duration of illness (p = 0.001) and types of treatment (p = 0.017) but the school functioning was only significantly associated with frequency of blood transfusion (p = 0.039). The psycho social health summary score was associated with age and education level (p = 0.037), duration of illness (p = 0.003) and types of treatment (p = 0.005). Therefore, for the total scale score was significantly associated with age and education level which p value = 0.042 respectively, race (p = 0.030) which the Indian significantly difference with Malay (p = 0.009) and Chinese (p = 0.019), types of beta thalassemia (p = 0.011), duration of illness and side effects of desferrioxamine treatment with p = 0.006 respectively and also the types of treatment (p < 0.001). Patients with not on any treatments will decrease of 16.47 units (p = 0.018), while those with no side effects of desferrioxamine treatment will increase of 14.60 units (p = 0.004) and every increases frequency of desferrioxamine treatment will increase of 2.30 units (p = 0.004), which were predicted physical functioning. The emotional functioning predictors were patients with not on any treatments will decrease of 18.87 units (p = 0.008) and every increases duration of illness will increase of 1.56 units (p = 0.009). Social functioning was predict the increases of age with increase of 1.66 units (p = 0.005), patients who were non-Malay with decrease of 16.27 units (0.004) and non beta thalassaemia major with decrease of 9.65 units (p = 0.014). Only patients with no side effects of desferrioxamine treatment was predicted by increase of 11.28 units (p = 0.047) of school functioning scores. Therefore, the predictors for psycho social health summary score and total scale score were patients with not on any treatment and increases frequency of blood transfusion with decrease of 29.87 units (p < 0.001) and decrease of 1.24 units (p = 0.023) of psycho social health summary score also decrease of 21.16 units (p < 0.001) but every increases frequency of blood transfusion will increase of 8.99 units (p = 0.018) of total scale score of health related quality of life.